Integrating Terminological Resources in Dictionary Portals: The Case of the Diccionarios Valladolid-UVa - Fuertes-Olivera, Pedro A.; Esandi-Baztan, M.A. (Lexikos, 2020)
This paper advocates the convergence of terminology and lexicography, and illustrates this view by presenting some of the steps taken for incorporating terminological resources and ideas in an online dictionary portal that is being constructed at the University of Valladolid (Spain). This dictionary portal contains several dictionary types, was designed by the same team and is being constructed from the same theoretical perspective, regardless of whether some of the lexical items included are judged "lexicographic", i.e. related to general language expressions, or "terminological", i.e. connected with terms. In addition to dealing with certain basic tenets of dictionary portals, the paper describes an ad-hoc typology of definitions that has been created for two main reasons. Firstly, it makes the process of compilation easier, more uniform, and more readily systematised, thus facilitating the efforts of different people in different places at different times. Secondly, these definitions will feed the Spanish–English Write Assistant, a commercially driven language tool that uses a language module based on statistics and is in the process of using Artificial Intelligence (AI) technologies, e.g. machine learning and neural networks, for creating patterns. We have found that precise definitions, similar to terminological (i.e. encyclopaedic) definitions, for most lemmas increase the tool's functions. Such definitions offer a very different picture of current monolingual Spanish and bilingual Spanish–English dictionaries.